1985
DOI: 10.2527/jas1985.602352x
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Criteria of Beef Bulls during and after Exposure to Increased Ambient Temperature

Abstract: Sixteen yearling Angus bulls were randomly assigned to one of two temperature-controlled chambers to determine the effects of elevated ambient temperature on body functions and semen characteristics. After 8 wk adjustment at 23 C, eight heat-stressed bulls were exposed to 35 +/- 1 C for 8 h and 31 +/- 1 C for 16 h during each 24-h period, and eight control bulls were maintained at 23 +/- 1 C for 8 wk. Then all bulls were exposed to 23 C for 8 wk. Bulls were fed so that both control and stressed bulls gained at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
0
6

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 0 publications
5
30
0
6
Order By: Relevance
“…Similar changes occurred at corresponding times in previous studies that involved increased testicular temperatures in bulls and rams (Howarth 1969;Meyerhoeffer et al 1985;Saab et al 2011;Rocha et al 2015;Hamilton et al 2016) with some apparent differences in the magnitude of changes and the interval from the thermal insult to recovery, attributed to the degree and duration of testicular heating and perhaps species-specific characteristics (Skinner and Louw 1966;Rathore 1970;Brito et al 2004;Nichi et al 2006). Furthermore, in this study, sperm damage occurred during the final stages of spermatogenic development in the testis (Howarth 1969;Cardoso and Queiroz 1988;Senger 2003).…”
Section: Discussionsupporting
confidence: 64%
“…Similar changes occurred at corresponding times in previous studies that involved increased testicular temperatures in bulls and rams (Howarth 1969;Meyerhoeffer et al 1985;Saab et al 2011;Rocha et al 2015;Hamilton et al 2016) with some apparent differences in the magnitude of changes and the interval from the thermal insult to recovery, attributed to the degree and duration of testicular heating and perhaps species-specific characteristics (Skinner and Louw 1966;Rathore 1970;Brito et al 2004;Nichi et al 2006). Furthermore, in this study, sperm damage occurred during the final stages of spermatogenic development in the testis (Howarth 1969;Cardoso and Queiroz 1988;Senger 2003).…”
Section: Discussionsupporting
confidence: 64%
“…HSPA1B plays a crucial role in the promotion of cell survival through refolding of damaged and unfolded proteins generated by stressful stimuli (Jäättelä 1999, Akerfelt et al 2007) and protects cells against DNA damage (Kotoglou et al 2009). Moreover, HSPA1B is involved in lightening the damage of hyperthermia on spermatogenesis and post-ejaculatory function of sperm (Meyerhoeffer et al 1985). It can protect cells from various stresses by inhibiting stress-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Meyerhoeffer et al (1985) reported that exposure to elevated ambient temperatures resulted in decreased bull semen quality as evidenced by a reduced percentage of motile sperm, reduced sperm output and an increased percentage of abnormal and aged sperm. Production Milk.…”
Section: Reproductionmentioning
confidence: 99%